Margaret Mead : the making of an American icon - Lutkehaus, Nancy (Princeton University Press, 2011)
Using photographs, films, television appearances, and materials from newspapers, magazines, and scholarly journals, this text explores the ways in which Margaret Mead became an American cultural heroine.